Local Wisdom Integration Training in PAIKEM Learning at MTs Salafiyah Syafi'iyah Mojokerto - Mochammad Yasir; Try Hartiningsih; Wiwin Puspita Hadi; Mochammad Ahied (Salus Publica: Journal of Community Service, 2024)
One form of student-centered learning is by integrating local wisdom into PAIKEM learning. Integrating local wisdom into PAIKEM learning is something new at MTs Salafiyah Syafi'iyah Mojokerto because teachers still rarely use local wisdom as a context and content of learning and its use in PAIKEM so that there needs to be community service in the form of training on integrating local wisdom into PAIKEM learning at MTs Salafiyah Syafi'iyah Mojokerto. The purpose of this activity is to train the skills of MTs Salafiyah Syafi'iyah Mojokerto educators in developing PAIKEM learning based on local wisdom to improve the quality of learning. The methods in this activity include (a) expository; (b) question and answer; (c) discussion; (d) demonstration; (e) FGD. The results of this community service activity are that there is an increase in the skills of MTs Salafiyah Syafi'iyah Mojokerto educators in developing PAIKEM learning based on local wisdom in the high category of 23 people and low category of 2 people. The results of these activities can be concluded that the training activities for integrating local wisdom into PAIKEM learning at MTs Salafiyah Syafi'iyah Mojokerto can improve the skills of educators in developing PAIKEM learning based on local wisdom to improve the quality of learning.